Peningkatan Hasil Belajar Menggunakan Model Problem Based Learning (PBL) pada Peserta Didik Kelas V SD Negeri 2 Tlahab Lor - Triyati, Triyati (Social, Humanities, and Educational Studies (SHES): Conference Series, 2020)
This study aims to improve the learning outcomes of fifth grade students of SD NEGERI 2 TLAHAB LOR in integrated thematic learning theme 9 using the Problem Based Learning (PBL) learning model. Integrated thematic learning is learning that uses theme in learning activities by combining several lesson content in each lesson. The hope of integrated thematic learning is that students can gain hands-on experience to be able to find their own various knowledge learned. So that learning is more meaningful. This research is a classroom action research conducted in two cycles. The research subjects were 26 students of class V. Data collection techniques used observation and learning outcomes tests. The results showed that the learning outcomes of the pre-action obtained the percentage of completeness 23.08% or 6 students who met the KKM with an average value of 47.16. In the first cycle of learning outcomes, the percentage of completeness was 34.62% or 9 students who met the KKM with an average score of 55.26. Cycle II learning outcomes obtained the percentage of completeness 57.69% or 15 students who meet the KKM with an average value of 66.88.